Kualitas Pelayanan Puskesmas Wonokusumo Kota Surabaya - Putri, Ajeng Kartika; Sjafi’i, Achmad (Universitas 17 Agustus 1945 Surabaya, 2018)
Health care still found deficiencies especially in the provision of drugs - drugs and medical equipment. Given the health services for the poor is a complex issue and the importance for human health, so that all human beings are entitled to proper health care. The existence of health centers in the community is important because health centers are the spearhead of health services provided by local governments. As for the support of this study, the authors used a qualitative descriptive method by taking the informant that the patient's health centers by means of interviews and documentation. Based on the results of this research is that the quality of service provided Wonokusumo PHC Surabaya to patients in accordance with the expectations of patients and patient satisfaction. Public Service Standards that become measure the quality of health center services Wonokusumo are: 1) Procedures, 2) Completion Time, 3) Cost of Services, 4) Product Services, 5) Infrastructures, 6) Competence Employer Services Officers. In this case the health centers have shown good service, procedures reasonably good service, turnaround time is still too long, lightweight and cost of the service fees paid in accordance with established, well service products seen from the results satisfactory services, facilities and infrastructure sufficient seen from amenities such as waiting rooms, bathrooms, parking lots, buildings and service rooms were comfortable and clean as well as medical equipment and drugs were complete, the competence of personnel service providers who are able, disciplined and friendly.Keywords: quality of service, public service